Access to HIV/STI testing among male and female Venezuelan migrants in Peru: evidence from a nationwide survey - Al-kassab-Córdova, Ali (2024)
Background: Human immunodeficiency virus (HIV) infection and sexually transmitted infections (STIs) are major global public health issues. Migrants represent a vulnerable group that faces multiple barriers to access to healthcare services, including HIV/STI testing. This study aimed to assess the factors associated with access to HIV/STI testing in male and female Venezuelan migrants in Peru. Methods: This was a cross-sectional study involving secondary data analysis of the 2022 Venezuelan Population Residing in Peru Survey. The study was conducted in the eight most populated cities inhabited by Venezuelan migrants and refugees. For each city, the sampling design was probabilistic, stratified, and independent. The outcome variable was whether participants had access to HIV or other STI testing during their stay in Peru. Statistical analysis was stratified by sex owing to potential effect modification. Crude and adjusted prevalence ratios were calculated using generalized linear models Poisson family with log link function. Confidence intervals were calculated to 95%. Results: A total of 3,723 male and 3,984 female migrants were included. Access to HIV/STI testing among male and female migrants was 19.85% and 25.16%, respectively. Among male migrants, being LGBTI, health insured, and married or cohabiting were associated with increased access to HIV/STI testing. Among females, those aged 18–44 years, those who were married or cohabiting and were health insured, and those residing for more than 1 year in Peru were significantly more likely to have access to HIV/STI testing. Moreover, physical/mental disability and unemployed status were associated with a lower probability of HIV/STI testing in females. Conclusions: Only two in ten Venezuelan migrants and refugees in Peru were screened for HIV/STI, with fewer males than females. Sex-specific sociodemographic, health-related, and migration-related variables were independently associated with access to HIV/STI testing.